Environmentally responsive design in Eastern Mediterranean. The case of vernacular architecture in the coastal, lowland and mountainous regions of Cyprus. (January 2017) - Philokyprou, Maria; Michael, Aimilios; Malaktou, Eleni; Savvides, Andreas
Abstract: Hundreds of years of empirical expertise resulted in the development of vernacular dwellings adapted to the local climate and geomorphology in order to accommodate the daily needs of the occupants. In this respect, vernacular architecture has a lot to teach contemporary architects and engineers in terms of environmentally responsive design. This paper reports on the findings of a field research and literature study that was undertaken in the framework of a two-year funded research programme which investigates the environmental design dimensions of rural vernacular dwellings in the coastal, lowland and mountainous regions of Cyprus which feature diverse topographical, geological and climatic characteristics. The investigation of a significant number of rural settlements led to the selection of representative case studies, as well as to the selection and tabulation of a large number of vernacular dwellings, in the settlements in question. Special attention was paid to the interrelation of the building typology, semi-open and open spaces configuration, materials, construction techniques and openings (size and position) with aspects of environmental design. A series of diverse bioclimatic design features, related to outdoor microclimatic control, passive cooling and heating techniques, were recorded in each climatic region. The research results note that vernacular architecture addresses successfully specific adaptation challenges imposed by local conditions.Moreover, it indicates that vernacular architecture presents itself as a model for a sustainable design approach. The findings of this study may be of interest in the broader Eastern Mediterranean region where similar typological, constructional and spatial characteristics are incorporated in vernacular architecture. Highlights: Vernacular architecture of Cyprus holds significant environmental value. Environmental aspects of traditional dwellings are identified in 3 climatic regions. Each climatic region exhibits diverse passive heating and cooling designs. This diversity is linked to the local climate, landscape, materials and way of life. A taxonomy of environmental techniques is proposed for each climatic region.